Approaches to polymeric mechanochromic materials. Issue 4 (4th December 2016) - Calvino, Céline; Neumann, Laura; Weder, Christoph; Schrettl, Stephen
ABSTRACT: Mechanochromic materials respond to mechanical stimuli with a change of their optical properties. Such materials are of interest for many technological applications and support fundamental research as they help improving the understanding of stress transfer in polymeric objects and aid in the identification of the processes that lead to mechanical failure. In this highlight, different approaches are discussed that permit the design of polymeric materials, which signal mechanical stresses through a chromic response. This highlight emphasizes materials that exhibit mechanically induced changes of their intrinsic absorption or emission properties. These responses almost exclusively originate from changes of molecular structure, conformational rearrangements, or disruption of intermolecular interactions. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 640–652 Abstract : Mechanochromic materials display a change of their optical properties on mechanical deformation. Such materials are of interest for technological applications as well as fundamental research and can aid in the identification of processes that lead to mechanical failure in polymeric objects. In this highlight, approaches toward polymeric materials that signal mechanical stresses through a chromic response are discussed. These responses almost exclusively originate from changes of molecular structure, conformational rearrangements, or disruption of intermolecular interactions.